AMPAS TAHU SEBAGAI NUTRISI Saccharomyces cerevisiae DALAM PEMBUATAN BIOETANOL DARI BERAS MERAH (Oryza nivara) DENGAN PROSES FERMENTASI - Monica Shara Sinaga (JURNAL KIMIA MULAWARMAN, 2020)
Research on the production of bioethanol from red rice flour starch (Oryza nivara) through enzymatic hydrolysis process and fermentation by Saccharomyces cerevisiae with the addition of tofu dregs as a nutrient source of microorganisms has been conducted. The process of bioethanol production consisted of hydrolysis, fermentation, distillation and ethanol content analysis using gas chromatography instrument. This research was conducted to determine the concentration of nutrients and the duration of fermentation to produce optimal ethanol levels. The hydrolysis process is carried out enzymatically through the liquification stage using ?-amylase and gluco-amylase at the saccharification stage. Then the fermentation process continued with a variation of 7, 8 and 9 days using Saccharomyces cerevisiae with the addition of tofu dregs concentration 0.5 %, 1 % and 1.5 % (w/v). The highest ethanol levels obtained from gas chromatography analysis was the addition of tofu dregs 1 % (w/v) and fermentation time for 8 days, with ethanol content obtained at 59.325 %.